Optimizing Leisure Agriculture by Analyzing Spatial Patterns and Tourists’ Perceptions: Evidence From Wuhan, China - Wang, Chengcheng; Wu, Shaohua; Yang, Wei; Bao, Haijun; Zhu, Jinxia; Wang, Xia (Frontiers in Environmental Science, 2022)
Leisure agriculture can meet the leisure needs of residents and promote farmers’ income, which is an important way to achieve rural revitalization. However, the unreasonable spatial patterns and weak competitiveness of leisure agriculture seriously restrict its sustainable development. This paper proposes a high-quality development path optimization framework of leisure agriculture, including: spatial pattern analysis of leisure agriculture based on big data; analysis of the quality of leisure agriculture based on tourists’ perceptions; and a high-quality development path optimization analysis of leisure agriculture integrating spatial patterns and tourists’ perceptions. Taking Wuhan City as an example, the results show that: 1) the main types of leisure agriculture are leisure farms, fishing, and picking garden, illustrating an agglomeration distribution pattern; 2) considering tourists’ emotional perceptions, most comments are positive, and leisure farm should enhance the experiences of tourists; 3) tourists’ dissatisfaction mainly involves environment, price, and travel, while product and service factors are relatively good; and 4) moderate agglomeration is beneficial to the quality of leisure agriculture, while excessive agglomeration has adverse effects. This study explores the development law of regional leisure agriculture, improves its theoretical research system and methods, and provides decision-making references for promoting the development of leisure agriculture.